Correlation of CXCL10, Tumor Necrosis Factor Receptor Type II, and Galectin 9 With Disease Activity in Juvenile Dermatomyositis. Issue 8 (August 2014) - Bellutti Enders, F.; van Wijk, F.; Scholman, R.; Hofer, M.; Prakken, B. J.; van Royen‐Kerkhof, A.; de Jager, W.
<x xml:space="preserve">Abstract</x> Objective Juvenile dermatomyositis (DM) is a systemic autoimmune disorder of unknown immunopathogenesis in which the immune system targets the microvasculature of skeletal muscles, skin, and other organs. The current mainstay of therapy is a steroid regimen in combination with other immunosuppressive treatments. To date, no validated markers for monitoring disease activity have been identified, which hampers personalized treatment. This study was undertaken to identify a panel of proteins specifically related to active disease in juvenile DM. Methods We performed a multiplex immunoassay for plasma levels of 45 proteins related to inflammation in 25 patients with juvenile DM in 4 clinically well‐defined groups, as determined by clinical activity and treatment. We compared them to 14 age‐matched healthy children and 8 age‐matched children with nonautoimmune muscle disease. Results Cluster analysis of circulating proteins showed distinct profiles for juvenile DM patients and controls based on a group of 10 proteins. In addition to CXCL10, tumor necrosis factor receptor type II (TNFRII) and galectin 9 were significantly increased in active juvenile DM. The levels of these 3 proteins were tightly linked to active disease and correlated with clinical scores (as measured by the Childhood Myositis Assessment Scale and physician's global assessment of disease activity on a visual analog scale). Conclusion Our findings indicate that CXCL10, TNFRII, and galectin 9 correspond to disease status in juvenile DM and thus could be helpful in monitoring disease activity and guiding treatment. Furthermore, they might provide new knowledge about the pathogenesis of this autoimmune disease.